Facing the darkness: A six-month follow-up of Infantile Neuroaxonal Dystrophy (Research, Society and Development, 2024)
Objectives: The objectives of this study were to report a case of Infantile Neuroaxonal Dystrophy, document the progression of neurological impairments over a period of 6 months, and apply a specific assessment scale.  Methodology: This study is an experimental case report with a descriptive approach, conducted through teleconsultation and remote monitoring, with the active participation of a physiotherapist who regularly attends to a 4-year-old female patient diagnosed with INAD. The study was submitted to the Ethics Committee of the State University of Paraiba (UEPB) and obtained approval with the number CAAE 74421623.3.0000.5187. The patient was assessed using the Pediatric Evaluation Form from the School Clinic of Physiotherapy (CEF) at UEPB and the Infantile Neuroaxonal Dystrophy Rating Scale (INAD-RS). Results: After the 6-month period, consisting of 30 physiotherapy sessions, twice a week, including stretching exercises and postures from the Neuroevolutionary Concept of Bobath, there was a regression in the child's functional performance, as evidenced by a decrease of 9 points in the INAD-RS score, indicating disease progression. Consequently, guidance was provided to the family environment and health-related advice was given to parents and caregivers.  Conclusions: This case report highlights the importance of prior knowledge about INAD, as well as the need for the use of specific assessment scales for its evaluation. It is believed that this study will contribute to furthering the scientific knowledge of professionals in the field. Therefore, the continuation of this research is necessary due to its clinical relevance.